Effect of Morphology of Co3O4 for Oxygen Evolution Reaction in Alkaline Water Electrolysis - Xu, Qi-Zhi; Su, Yu-Zhi; Wu, Hao; Cheng, Hui; Guo, Yun-Ping; Li, Nan; Liu, Zhao-Qing (Current Nanoscience, 2015)
In this paper, three different morphological Co3O4 electrodes for oxygen evolution reaction (OER) have been synthesized. By comparing the three morphologies of Co3O4, the electrocatalytic properties show that the urchin-like spheres of Co3O4 electrode has relative low overpotential and good electrocatalysis stability, indicating that the structure of urchin-like Co3O4 spheres exhibit an easy OER for water splitting.
Keywords: oxygen evolution reaction